2006
DOI: 10.1097/00008877-200609000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of modafinil in a marmoset Parkinson model: behavioral and neurochemical aspects

Abstract: The vigilance-enhancing agent modafinil has neuroprotective properties: it prevents striatal ischemic injury, nigrostriatal pathway deterioration after partial transsection and intoxication with 1-methyl-1,2,3,6-tetrahydropyridine. The present study determines the protective effects of modafinil in the marmoset 1-methyl-1,2,3,6-tetrahydropyridine Parkinson model on behavior and on monoamine levels. Twelve marmoset monkeys were treated with a total dose of 6 mg/kg 1-methyl-1,2,3,6-tetrahydropyridine. Simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 43 publications
1
26
0
2
Order By: Relevance
“…Future studies should address the impact of the selected frequency band (here 12–17 Hz) to demonstrate SMR specificity and help elucidate the role of controversially discussed basal ganglia‐thalamocortical rhythms 20, 21, 22, 23, 24. We showed that SMR neurofeedback reduced monkeys’ heart rate close to anesthesia levels (206–245 beats/min)25 and improved HTT mood scores,16 in accordance with findings in normal humans 10…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Future studies should address the impact of the selected frequency band (here 12–17 Hz) to demonstrate SMR specificity and help elucidate the role of controversially discussed basal ganglia‐thalamocortical rhythms 20, 21, 22, 23, 24. We showed that SMR neurofeedback reduced monkeys’ heart rate close to anesthesia levels (206–245 beats/min)25 and improved HTT mood scores,16 in accordance with findings in normal humans 10…”
Section: Discussionsupporting
confidence: 82%
“…average of 4 subsequent pre‐study days). Before noon monkeys’ emotional mood was assessed with the Human Threat Test (HTT)16 before (baseline), three times during the training phase and five times during L‐DOPA treatment. Baseline was set to 100%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These markers are sensitive to reflect neurodegeneration and neuroprotection in the MPTP marmoset model [24]. The parkinsonian symptoms are assessed by using two extensive behavioral observation scales for PD and functional tests measuring locomotor activity and hand-eye coordination (HEC) [25,26].…”
Section: Introductionmentioning
confidence: 99%